The Stewardship of School Counselor Education in Higher Educational Establishments - Kozhabergenova, Gaukhar E.; Taubaeva, Sharkul; Bulatbayeva, Aygul A.; Kabakova, Maira P.; Asanov, Naukhan A. (Opción, 2019)
Social Pedagogy is a new discipline in Kazakhstan. The issues regarding the quality counselor education remain under attention of researchers in education management, as the number of grants for this specialization grows from year to year, so as the regional demand for competent counselors. Government control and employer oversight are being tightened, while the range of problems that counselors face increases. Besides, innovation processes in education are channeled either towards maintaining the existing level of quality or towards reaching an even higher level. This article intends to analyze the methodological support of quality assurance in counselor education at the university.